Congenital coronary artery fistulae: a rare cause of heart failure in adults - Geller, Charles M (BioMed Central, 2014)
Coronary artery fistulae are uncommon, reported in 0.25% of patients undergoing coronary angiography. Two patients with congenital coronary artery fistula and coronary artery disease who presented with symptoms of exacerbated congestive heart failure out of proportion to their atherosclerotic burden were successfully treated by epicardial fistula ligation and coronary artery bypass grafting with marked improvement in functional status.